IMPLEMENTATION OF CULTURE ORGANIZATION FOR INCREASING CUSTOMER SATISFACTION AT PT BANK RAKYAT INDONESIA UNIT PLUMBON - Ayu Lestari, Ni Wayan Fitriana; Dewi, Isti Riana (Jurnal EBI, 2023)
The BRI Unit Plumbon Branch Office is a branch office that has a branch office service function in Cirebon. BRI branch offices are branch offices that carry out the function of collecting funds from the public in the form of savings and distributing them to the public in the form of credit or other means to improve people's lives. This study aims to identify and analyze the organizational culture model and the application of organizational cultural values at PT. Bank Rakyat Indonesia Cirebon Plumbon Unit so that they know what needs to be repaired and maintained. Organizational culture models and the application of organizational cultural values were identified and analyzed from organizational structure, human resource management policies, integrity, professionalism, customer satisfaction, exemplary and respect for human resources. This researcher used a purposive sampling technique. Data collection methods in-depth interviews and documentation. The results show that the organizational culture model and the application of organizational cultural values tend to show problems in terms of integrity and professionalism. The value of integrity tends to be lacking because the tenure is too short for contract workers, so organizational culture is not well understood, especially those at the forefront of service. Professionalism shows that most of the frontline services are contract workers who are given short training, so that knowledge of BRI products is lacking.Keywords: customer satisfaction, organizational culture, organizational cultural values